Lessons of housing policy in chile (2006)
This article presents a retrospective analysis of the housing policies in Chile, focused in the revision of the laws that have allowed their development, as well as in the participation of the sectors public and private. This analysis has located the beginning of habitudinal problematic in the first years of the dictatorship, moment at which the capitalist system opens a particular road in Latin America reflected in a fruitful way in the Nineties. The article at the same time approaches the historical tensions between the informal sectors and the system, establishing a clear comparison between processes, policies, and objective population.